Effect of periodontal therapy on serum and salivary Interleukin-1 beta (IL-1β) and malondialdehyde levels in chronic periodontitis: Periodontal therapy and serum and IL-1β and MDA - T. Nanakaly, Haween; Nouri Ahmed, Sardar; Warya Azeez, Hozan (Cellular and Molecular Biology, 2024)
Chronic periodontitis (CP) is distinguished by an inflammatory reaction and the presence of oxidative stress (OS), which has consequences for overall health. Interleukin-1β (IL-1β) and malondialdehyde (MDA) serve as markers of inflammation and OS, respectively. Analyzing the alterations in their reaction to periodontal therapy can provide valuable insights into the management and monitoring of CP progression. The current study aimed to evaluate the impact of non-surgical periodontal therapy (NST) on IL-1β and MDA levels in the serum and saliva of CP patients and explore their correlation with clinical periodontal indices post-therapy. There were 60 participants in this research, aged 33 to 50, equally split between thirty periodontally healthy controls and 30 patients with CP. Measures were taken of the clinical periodontal parameters, including the bleeding index, probing pocket depth, gingival index, and plaque index. Saliva and blood samples were collected for IL-1β and MDA analysis using ELISA and spectrophotometrically. CP patients received scaling and root planning (SRP) as part of phase I periodontal therapy, and after six weeks, we reevaluated clinical parameters and IL-1β and MDA levels. In CP patients, both saliva and serum IL-1β and MDA levels significantly increased alongside worsening clinical periodontal parameters compared with periodontally healthy individuals. phase I periodontal therapy led to a notable decrease in both saliva and serum IL-1β and MDA levels, accompanied by improvements in clinical parameters. Additionally, following six weeks of scale and root planning treatment, our data showed a strong positive relationship between salivary IL-1β and MDA levels with PPD and CAL. SRP therapy is effective in managing periodontal health, as evidenced by a significant decrease in clinical parameters and biomarker levels after treatment for CP patients. This suggests that salivary IL-1β and MDA may be useful biomarkers for indicating the severity of periodontal disease and the effectiveness of treatment.